2017
DOI: 10.1186/s12936-017-2092-5
|View full text |Cite
|
Sign up to set email alerts
|

A single rapamycin dose protects against late-stage experimental cerebral malaria via modulation of host immunity, endothelial activation and parasite sequestration

Abstract: BackgroundMaladaptive immune responses during cerebral malaria (CM) result in high mortality despite opportune anti-malarial chemotherapy. Rapamycin, an FDA-approved immunomodulator, protects against experimental cerebral malaria (ECM) in mice through effects on the host. However, the potential for reduced adaptive immunity with chronic use, combined with an incomplete understanding of mechanisms underlying protection, limit translational potential as an adjunctive therapy in CM.ResultsThe results presented he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Fludarabine, a purine analogue, and treosulfan, an alkylating agent, are assumed to interfere with helminths' cell cycle and with human bone marrow cells . The immunosuppressive agents sirolimus and MMF also might have had a strong effect on the worm's cell cycle …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fludarabine, a purine analogue, and treosulfan, an alkylating agent, are assumed to interfere with helminths' cell cycle and with human bone marrow cells . The immunosuppressive agents sirolimus and MMF also might have had a strong effect on the worm's cell cycle …”
Section: Discussionmentioning
confidence: 99%
“…15 The immunosuppressive agents sirolimus and MMF also might have had a strong effect on the worm's cell cycle. [16][17][18][19][20]…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, a similar study revealed the protective properties of rapamycin in experimental CM. This study indicated that rapamycin induced the reduction of neuropathology and death via the regulation of host responses to CM infection (Mejia et al 2017 ). After the treatment with rapamycin, the parasite cytoadherence was inhibited through the downregulation of CD36 in peripheral organs such as white adipose tissue.…”
Section: Introductionmentioning
confidence: 94%
“…The administration of rapamycin in infected mice with CM blocked the breakdown of the blood–brain barrier, reduced the brain hemorrhage, and increased the survival rate of infected mice demonstrating the immunoregulatory functions of mTOR as well as the therapeutic properties of rapamycin in CM. In addition, such a treatment diminished the influx of T cells (CD4 and CD8) into the brain and reduced the accumulation of infected erythrocytes in the brain of infected mice with CM (Gordon et al 2015 ; Mejia et al 2017 ). Moreover, leukocyte trafficking to the brain and leukocyte proliferation in the brain was blocked in infected mice treated by rapamycin (Gordon et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sequestration of iRBCs can also be prevented by the use of drugs targeting cytoadherence of iRBCs. Rapamycin prevents the cytoadherence of iRBCs via reduction of ICAM-1 and VCAM-1 expression in ECM [29]. Moreover, ethanolic extracts of the fungus Trichoderma stromaticum decrease inflammation and ameliorate ECM by reducing cerebral expression of ICAM-1 and VCAM-1, thereby preserving BBB integrity [30].…”
Section: Key Figurementioning
confidence: 99%